Curcumin as a Natural Modulator of B Lymphocytes: Evidence from In Vitro and In Vivo Studies - Mohammadi, Asadollah; Mashayekhi, Kazem; Navashenaq, Jamshid G.; Haftcheshmeh, Saeed Mohammadian (Mini Reviews in Medicinal Chemistry, 2022)
B cells are the only player of humoral immune responses by the production of various types of antibodies. However, B cells are also involved in the pathogenesis of several immune-mediated diseases. Moreover, different types of B cell lymphoma have also been characterized. Selective depletion of B cells by anti-CD20 and other B cell-depleting agents in the clinic can improve a wide range of immune-mediated diseases. B cells' capacity to act as cytokine-producing cells explains how they can control immune cells' activity and contribute to disease pathogenesis. Thus, researchers investigated a safe, low-cost, and effective treatment modality for targeting B cells. In this respect, curcumin, the biologically active ingredient of turmeric, has a wide range of pharmacological activities. Evidence showed that curcumin could affect various immune cells, such as monocytes and macrophages, dendritic cells, and T lymphocytes. However, there are few pieces of evidence about the effects of curcumin on B cells. This study aims to review the available evidence about curcumin's modulatory effects on B cells' proliferation, differentiation, and function in different states. Apart from normal B cells, the modulatory effects of curcumin on B cell lymphoma will also be discussed.
Keywords: B cells